1976
DOI: 10.1111/j.1432-1033.1976.tb10789.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proteins Synthesized in Mitochondria of Cultured Mammalian Cells. An Assessment of Current Approaches and Problems in Interpretation

Abstract: The conditions which enable highly efficient utilization of [35S]methionine by cultured mammalian cells and the resolution of selectively labelled mitochondrial products are described. Analysis of mitochondria purified from cells labelled in the presence or absence of inhibitors of cytoplasmic (or mitochondrial) protein synthesis indicated that about 5% of the [35S]Methionine incorporated into mitochondrial proteins results from synthesis on mitoribosomes. The electrophoretic profile of the detergent‐solubiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
0
7
1
1
Order By: Relevance
“…Electrophoretic analysis of the mitochondrially-translated peptides indicated that these products were stable after 3 h chase, and that the relative distribution of radioactivity between the various peaks did not differ significantly from that shown in fig.3. These findings again provide no support for an interconversion between the peptides [7]. They also indicate that breakdown of newly synthesized proteins is negligible under the conditions of our experiments.…”
Section: Resultscontrasting
confidence: 75%
“…Electrophoretic analysis of the mitochondrially-translated peptides indicated that these products were stable after 3 h chase, and that the relative distribution of radioactivity between the various peaks did not differ significantly from that shown in fig.3. These findings again provide no support for an interconversion between the peptides [7]. They also indicate that breakdown of newly synthesized proteins is negligible under the conditions of our experiments.…”
Section: Resultscontrasting
confidence: 75%
“…Whole cell lysates (40 μ g) were electrophoresed through 12% SDS-PAGE. The gels were dried on 3MM chromatography paper (Whatman), and the total intensities of the signals were quantified by phosphorimaging analyses (Jeffreys and Craig, 1976). The siRNA mediated knock-down efficiency of the corresponding mitochondrial ribosomal protein was confirmed with immunoblotting analysis of whole cell lysates or crude ribosomal fractions, prepared as stated above.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial protein translation was assessed as described (29) by incorporation of 35 S-methionine in cells wherein cytoplasmic protein synthesis was inhibited by cycloheximide. Briefly, confluent cell cultures were washed twice in PBS, incubated in cysteine- and methionine-free Dulbecco’s Modified Eagle Medium (Cellgro) for 10 min at 37°C under an atmosphere of 5% CO 2 in air and subsequently incubated for 1 h with cycloheximide (10 μg/ml).…”
Section: Methodsmentioning
confidence: 99%